Involvement of L-carnitine in cellular metabolism: Beyond Acyl-CoA transport - Chapela, Sebastián Pablo (2009)
Carnitine is well-known for its role in the transport of fatty acids to the mitochondrial matrix, where β-oxidation takes place. This work describes novel functions for this compound and novel data on its pharmacokinetics.